Ketamine-assisted psychotherapy, psychedelic methodologies, and the impregnable value of the subjective—a new and evolving approach - Wolfson, Phil; Vaid, Gita (Frontiers in Psychiatry, 2024)
Psychiatry is in a growth phase in which several psychedelic medicines have entered its arena with great promise. Of these, presently, ketamine is the only medicine that may be le-gally prescribed. We hypothesize that at subanesthetic doses, ketamine produces a unique spectrum of altered states, ranging from psychoactive to deep ego dissolving experiences, that are intrinsic to ketamine’s therapeutic effects. When these experiences are embedded in a therapeutic relationship—a setting--that fosters an amplification of the recipient’s subjective consciousness, personal growth, inner healing, greater clarity, and better relationships may well ensue. While much of the literature on ketamine labels its dissociative effects as ‘side ef-fects’, alteration of consciousness is a component and unavoidable ‘effect’ of its therapeutic impact. From its inception in the clinical trials of the 1960s, ketamine was recognized for producing dissociative, psychedelic effects on consciousness in subjects as they emerged from ketamine-induced anesthesia. Unanticipated and unintegrated, these experiences of “emergence phe-nomena” were felt to be disturbing. Accordingly, such experiences have been typically labelled as dissociative side-effects. However, in a conducive set and settings these experiences have been demonstrated to be of positive use in psychiatry and psychotherapy, providing a time-out from usual states of mind to facilitate a re-shaping of self-experience along with symptomatic relief. In this way, ketamine assisted psychotherapy (KAP) offers a new potential in psychiatry and psychotherapy that is powerfully valanced towards recognizing experience, individuality, and imagination. Essential to a successful therapeutic experience and outcome with KAP is close attention to the subjective experience, its expression by the recipient and integration of the ketamine experience as a healing opportunity.